Self-Efficacy Development in Rachael Lippincott’s Five Feet Apart - Harindah, Valerie J. M.; Wuntu, Ceisy N.; Posumah, Jeni (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study analyzed Stella Grant’s self-efficacy development portrait in the novel Five Feet Apart by Rachael Lippincott. Self-efficacy refers to people’s belief in themselves and their ability that they are capable of accomplishing goals. This research focus on Stella Grant as the protagonist to find evidence of Stella’s self-efficacy development. This study used qualitative descriptive method which the results are in the form of words, and where the data were collected by primary and secondary sources. The primary data were collected from Five feet Apart novel and the secondary data were from articles, journals, e-journals, books, e-books and any other sources.The data analysis used psychological approach and used the concept of self-efficacy expounded by Albert Bandura in his work, Self-efficacy : The exercise of control (1997). The result showed that there are four sources that influenced Stella’s self-efficacy namely mastery experience, social modeling, verbal persuasion and physiological and emotional state. Among those sources, verbal persuasion and physiological & emotional state contribute the most in influencing Stella’s sense of self-efficacy